Komodifikasi Agama Sebagai Masalah Dakwah - Moch. Fakhruroji (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
The meaning of religion, in its material manifestation, has been reduced through times into a narrow meaning. The system of global capitalism seems to be successful in dividing our logical paradigm apart as to make it classified according to choices solely based on private needs. Religion has come to bear merely personal function without social relevance. There has to be creative attempts in re-actualizing religion as to perform extended functions. Religion has to be both relevant and in accord with public interests and social issues.